COMPARATIVE ANALYSIS OF THE POSITIVIST AND INTERPRETIVE PARADIGMS IN QUALITATIVE RESEARCH (A Study of Research Methodology in Social Science) - Winda Kustiawan; Atika Syalsabila Putri; Fahira Rahmah Hani; Nafiis Satria Pratama; Fadhlan Rizky Hazmar Firdaus Ritonga (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
: This study aims to analyze and compare two major paradigms in qualitative research methodology: the positivist paradigm and the interpretive paradigm. These paradigms differ fundamentally in their ontological, epistemological, and axiological assumptions, which influence how researchers perceive social reality, construct knowledge, and determine methodological approaches. The positivist paradigm emphasizes objectivity, empirical verification, and generalizability, whereas the interpretive paradigm focuses on subjective understanding, social context, and meaning-making. Using a descriptive qualitative approach through literature review, this research explores the strengths and limitations of each paradigm and their relevance in the context of contemporary social research. The findings indicate that paradigm selection must be aligned with the research objectives and the nature of the phenomena being investigated. This study is expected to provide conceptual contributions to researchers in establishing an appropriate methodological foundation for qualitative research.